Suggestiiviset mielikuvamallit käyttäytymisen muokkaajina tarkkailuluokkalaisilla - Lindh, Raimo (1987)
The applied object of this research was to evaluate a developed suggestive method as a part of special education for disturbed pupils. What was asked basically was which of the following alternatives would best support the development of personality traits, attitudes, achievement and conduct: (1.) Audio-recorded suggestive Covert Modeling program during special education (18' 50") (experimental group 1, treatment X₁), (2.) Audio-recorded suggestive Covert Modeling program during special ed6cation (9'50") (experimental group 2, treatment X₂), (3.) Ordinary special education (control group, treatment X₀). Because the number of disturbed pupils was considerable large, (N = 195) it also gave an opportunity to examine the quality and structure of the environment, attitudes, self-image and achievement motivation of these pupils. The theoretical object of the project was to test Bandura's (1977 and 1980) Self-Efficacy Theory of how Self-Efficacy Expectations affect the change of behavior with this group of persons. Suggestive programs were presented to experimental groups once a week during six weeks. Time span from pre-test to post-test was four months (groups 1, 2, 3; N = 80, 49, 66) and to follow up -test eight months (groups 1, 2, 3; N = 26, 14, 23). Descriptive results showed generally positive attitudes, achievement motivation and self-image. These pupils' material environment was satisfactory in this survey. So for example connections between environment and transition to special education might be found in the lability of family structure, parents' minimal basic and professional education and the status of profession. Main results of the explaining problems were that anxiety could be explained by expected employment after school, parents' health, job dissatisfaction and smoking habit. Achievement was best explained by the lenght and place of education after school. All experimental results were tested by the covariance analysis pre-test scores being covariates in each variable. One of the main results was the fact that used treatments within this short intervention did not affect change in either regular of remedial achievement. In the area of experiencing personality states, learning of mental relaxation seemed to relieve anxiety somewhat through treatment X₁ compared to the effects of treatment X₂ (F = 6.72, p<.05 follow up -test) and treatment X₀ (F = 3.50. p = symptomatic significance follow up -test). Temporarily this relievance freed behavior in orientation and personal social behavior compared to treatment X₀ (X₁ <X₀, F = 5.39, p<.05 and F = 9.82, p>.01 follow up -test). Both treatments of the experimental groups caused a change in attitudes towards school compared to the control group treatment. The scores decreased (X₁ <X₀, F = 4.25, p<.05 and X₂<X₀, F = 4.84, p<.05 follow up -test). The change was interpreted to be happened in a realistic direction. When the results were examined in the light of Self-Efficacy Theory it could be stated that relievance of anxiety and attitude change could result for the growth of Self-Efficacy Expectations. That is why pupils could evaluate themselves more positively and could express their attitudes in a more realistic way than before.